User Interface (UI) Design Waste Management Application using Design Thinking Method - Yevi Septiray Purbo; Azis, Abdul; Hidayah, Debby Ummul (LPPM Universitas Potensi Utama, 2024)
Waste management remains a significant challenge, particularly in developing countries like Indonesia, where urbanization and increasing consumption contribute to rising waste volumes. Kesugihan District in Cilacap Regency faces similar issues, necessitating innovative solutions. This study aims to optimize the user interface (UI) design of a waste management application using the Design Thinking approach, ensuring usability and effectiveness in engaging users. Through iterative design stages Empathize, Define, Ideate, Prototype, and Testing this research incorporates user needs and feedback into UI development. The usability of the designed UI was evaluated using the System Usability Scale (SUS), achieving scores of 71 for users and 70 for administrators, categorizing the interface as “Good”. Comparative analysis with similar waste management applications demonstrated superior navigation, clearer information presentation, and enhanced user engagement in the proposed UI. Additionally, user feedback highlighted areas for improvement, including navigation clarity, onboarding tutorials, and response speed optimization. This study contributes to the field of waste management technology by demonstrating how Design Thinking can enhance UI usability and user experience. Future work should explore integrating AI for personalized recommendations, gamification elements for increased participation, and broader usability testing across diverse demographics to further refine the application’s effectiveness.